FAKTOR KRUSIAL PENYEBAB DESA TERTINGGAL - Arifuddin Arifuddin; Tajuddin Tajuddin; La Ode Almana; Adwi Adwi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the crucial factors that cause villages in Muna Regency, Southeast Sulawesi, to remain classified as underdeveloped. The research utilizes secondary data from the 2024 Village Development Index (Indeks Desa Membangun/IDM), with the unit of analysis consisting of 21 villages categorized as underdeveloped. The results indicate that social and environmental aspects are not the main constraints, as most villages show relatively good performance in the Social Resilience Index and the Environmental Resilience Index. This suggests that social conditions and environmental management in these villages are generally adequate. In contrast, economic factors are identified as the fundamental root of the problem. All underdeveloped villages are classified as “Critical” in the Economic Resilience Index, reflecting weak economic structures and limited productive activities. These findings confirm that village underdevelopment in Muna Regency is driven by structural economic issues. Therefore, a reorientation of development policies is required, particularly by shifting budget priorities from predominantly social programs toward productive and sustainable economic stimulus initiatives.